Implementation of Physical Education and Sports Learning Health at SD Laboratorium UNU Blitar - Imawati, Veni (Global Education Journal, 2025)
This study aims to analyze the implementation of learning design suitability, learning implementation, and PJOK learning evaluation with the independent learning curriculum. This research is a quantitative descriptive study. This research was conducted at the UNU Blitar Laboratory Elementary School using purposive sampling, with a sample size of 28 students. It can be concluded that overall, the achievement level in the implementation of learning reached 62%. Each aspects studied, namely: (1) PJOK learning planning with an achievement percentage of 53.02% or in the Fair category; (2) PJOK learning implementation with an achievement percentage of 76.60% or in the Good category; and (3) PJOK learning evaluation with an achievement of 51.81% or in the Fair category.